2018
DOI: 10.1039/c8nj00201k
|View full text |Cite|
|
Sign up to set email alerts
|

Transformation of the surface compositions of titanium during alkali and heat treatment at different vacuum degrees

Abstract: The AH method at different vacuum degrees had a significant influence on the surface composition, structure, wettability, bioactivity and other properties of titanium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…10 5 -10 −3 Pa) [149]. Their results showed that at higher vacuum pressures, the structure exhibited larger pores sizes, while improving the HA formability in SBF [149]. Takedama et al postulated that the formation of apatite on alkali-treated titanium occurred through electrostatic interactions between the surface, and specific ions within the aqueous solution [14].…”
Section: Apatite Formation Mechanism Of Alkali-titanate Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…10 5 -10 −3 Pa) [149]. Their results showed that at higher vacuum pressures, the structure exhibited larger pores sizes, while improving the HA formability in SBF [149]. Takedama et al postulated that the formation of apatite on alkali-treated titanium occurred through electrostatic interactions between the surface, and specific ions within the aqueous solution [14].…”
Section: Apatite Formation Mechanism Of Alkali-titanate Surfacesmentioning
confidence: 99%
“…explored vacuum pressures during the heat treatment process (ca. 10 5 –10 −3 Pa) [149]. Their results showed that at higher vacuum pressures, the structure exhibited larger pores sizes, while improving the HA formability in SBF [149].…”
Section: Medical Alkaline Titanatesmentioning
confidence: 99%
See 1 more Smart Citation